Comparison of secondary breakup models for droplet-laden compressor flows. (July 2019) - Storm, C.; Joos, F.
Highlights: The DPF code predicts well the Weber numbers within a droplet-laden compressor flow. The applicability of a simplified implementation of the NLTAB3 model is approved. Maximum deformation plots reveal the disparity between applied TAB and NLTAB3 model. Breakup criteria from shock tube results show deficiency in gradually accelerated flow. One recombined secondary breakup model is identified to reproduce experimental results. Abstract: Different secondary breakup models are assessed to simulate gas-droplet flows that involve large velocity gradients and yield relative velocities between both phases (e.g. wet compression flows). For the simulation of such two-phase flows, the Euler-Lagrange approach is employed, using a commercial flow solver and an in-house FORTRAN source code. The droplet deformation models: Taylor Analogy Breakup (TAB) and a simplified implementation of the Non-linear TAB (NLTAB3) are each tested with two different breakup criteria to evaluate the adequacy for considered droplet-laden compressor flows. A detailed atomization model is applied to account for a temporal fragmentation process. By contrast with experimental results good agreements are found for Weber number distributions in the inter blade flow. Though, different sensitivities and locations for secondary breakup occurrence are observed in dependence of applied droplet deformation model and breakup criterion. In spite of incisive model simplifications to reduce its computational effort, the non-linear droplet deformation model (NLTAB3) in combination with a physically substantiated breakup criterion showed good agreements with qualitative experimental data.